1993
DOI: 10.1111/j.1365-2362.1993.tb00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal dexamethasone effectiveness in the treatment of hypersensitivity pneumonitis in mice

Abstract: The effects of daily intranasal instillation of liposomal dexamethasone and free dexamethasone phosphate were compared in a murine model of hypersensitivity pneumonitis induced by Saccharopolyspora rectivirgula (formally known as Micropolyspora faeni). After 3 weeks of antigen and liposome instillations, lung response was evaluated by bronchoalveolar lavage cell counts, lung index and histopathology. Systemic absorption was evaluated by measuring plasma adrenocorticotropic hormone (ACTH) level. Free dexamethas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…6a). These results are in agreement with the ability of inhaled free Dex at a dose of 0.5 mg/kg to cause strong inhibition of neutrophil accumulation in the lung after stimulation with diesel particles (Nemmar et al, 2004) and pneumonitis antigen (Tremblay et al, 1993). It has been accepted that selective delivery of the therapeutic agents into the target site increases drug efficacy and decreases side effects (Takakura and Hashida, 1996).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…6a). These results are in agreement with the ability of inhaled free Dex at a dose of 0.5 mg/kg to cause strong inhibition of neutrophil accumulation in the lung after stimulation with diesel particles (Nemmar et al, 2004) and pneumonitis antigen (Tremblay et al, 1993). It has been accepted that selective delivery of the therapeutic agents into the target site increases drug efficacy and decreases side effects (Takakura and Hashida, 1996).…”
Section: Discussionsupporting
confidence: 77%
“…There are several reports about the application of liposomes to incorporate dexamethasone (Dex), a potent GC, for lung inflammation by intratracheal (i.t.) administration (Tremblay et al, 1993;Suntres and Shek, 2000); however, difficulties in controlling the drug incorporation and retention in liposomes have been reported (Shaw et al, 1976). Benameur et al (1993) demonstrated that dexamethasone palmitate (DP), which is more lipophilic than Dex, was inserted in the lipid bilayer and showed significant encapsulation and retention in the liposomes.…”
Section: Inhalation Of Lipopolysaccharide (Lps)mentioning
confidence: 99%
“…Tremblay et al [16] used liposomal dexamethasone for intrainstillation in mice to investigate the effect on hypersensitivity pneumonitis and could demonstrate a stronger effect of the liposomal formulation versus the free compound. Mishina and Jusko [17] tested the dose-proportionality and chronic-dose pharmacokinetics of liposomal methylprednisolone in male Lewis rats and found a nonlinear disposition and an irregular pharmacokinetics.…”
Section: Discussionmentioning
confidence: 98%
“…There are a number of literature reports concerning liposome formulations of dexamethasone and other glucocorticoids (Bonanomi et al, 1987;Taniguchi et al, 1987;Tremblay et al, 1993;Benameur et al, 1995;Kulkarni and Vargha-Butler, 1995;VarghaButler and Hurst, 1995;Farshi et al, 1996;Lopes de Menezes and Vargha-Butler, 1996;Al-Muhammad et al, 1996;Al-Muhammed et al, 1996;DiMatteo and Reasor, 1997;Saarinen-Savolainen et al, 1997;Suntres and Shek, 1998;Kallinteri et al, 2002;Metselaar et al, 2002;Cevc and Blume, 2004;Chono and Morimoto, 2006;Koning et al, 2006;Tsotas et al, 2007). However, the physicochemical properties of these liposomes vary considerably.…”
Section: Introductionmentioning
confidence: 93%
“…The encapsulation of dexamethasone in carrier systems such as liposomes and microspheres can diminish the adverse effects and reduce the total amount of drug required. Liposomal and microsphere dexamethasone formulations have been investigated for hypersensitivity pneumonitis (Tremblay et al, 1993); ophthalmic anti-inflammatory action (Taniguchi et al, 1987(Taniguchi et al, , 1988Al-Muhammad et al, 1996;Al-Muhammed et al, 1996); oral ulcers (Farshi et al, 1996); arthritis (Bonanomi et al, 1987;Koning et al, 2006); atherosclerosis (Chono et al, 2005a,b;Chono and Morimoto, 2006); dermatological conditions (Cevc and Blume, 2004); pulmonary diseases (Benameur et al, 1995;Suntres and Shek, 1998); silica-induced pulmonary toxicity (DiMatteo and Reasor, 1997); localized anti-inflammatory effect for metallic stents (Kallinteri et al, 2002); brain edema (Eroglu et al, 2001); and controlling the inflammatory response to implantable devices (Hickey et al, 2002b,a).…”
Section: Introductionmentioning
confidence: 99%